Macro-Factors' Impact on Stock Returns: Insights from Exchange-Diversified Shares: Dampak Faktor Makro terhadap Return Saham: Wawasan dari Saham yang Terdiversifikasi di Bursa - Mochamad Rizal Yulianto; Dafita Wahyu Mekarsari; Heri Widodo; Nurasik Nurasik; Bayu Hari Prasojo (Academia Open, 2023)
This study investigates the impact of fundamental and macroeconomic factors on diversified stock returns, crucial for investment decisions. Employing purposive sampling, key analysis methods included coefficient of determination (R2), multiple regression, paired t-tests, and classic assumption tests. Results reveal that inflation, market price, profitability, and leverage insignificantly affect share prices, challenging conventional assumptions. These findings underscore the need for a reevaluation of factors influencing stock returns, prompting a rethinking of investment strategies and risk assessment in global markets. Highlights : Methodological Rigor: Utilized purposive sampling and robust statistical techniques like regression and t-tests to analyze the impact of diverse factors on stock returns. Challenging Conventional Wisdom: Findings contradict traditional assumptions about the influence of inflation, market price, profitability, and leverage on share prices. Implications for Investment Strategy: Emphasizes the necessity for a paradigm shift in investment strategies, urging a reassessment of risk evaluation and decision-making processes in global markets. Keywords : Stock returns, Fundamental factors, Macroeconomic factors, Investment decisions, Risk assessment